Impact of climate change and macroeconomic factors on Malaysian agriculture production - Fawad, Entezari Ahmad (2020)
Agriculture sector is one of the important sectors that contributed 8.6% of the national Gross Domestic Product and about 12.1% of the total labour force in 2016. In general, the production system in agriculture sector is totally different from other economic sectors such as manufacturing and services. This is because agricultural production is not just based on labour and capital, but it is also highly related to the climate variables i.e., rainfall, temperature. Therefore, the agriculture sector, especially crop production is affected biophysically by climatic variables such as temperature and rainfall. Past studies have indeed proven and demonstrated the negative effect of climate change on agricultural production. This indicates that climate change reduces agricultural production and consequently, endangering food security. In Malaysia, temperature has increasing trend and rainfall showed acute fluctuations. Prolong raised temperature and rainfall fluctuations cause climate disasters such as flood and drought which lead to declining in agricultural production. In addition to this, the agriculture production is also constrained by the economic factors. For instance, the agriculture employment in Malaysia recorded substantial declines in the years of 1982, 1997, 2001, 2011 and 2016, corresponding with the decline in agriculture gross domestic product growth. However, the effect of climate variables is not considered in the agricultural production function in majority of the past studies. Thus, this study included the climate variables (rainfall and temperature) in to the production function with macroeconomic factors to examine the impact of climate change and macroeconomic factors on the Malaysia’s agricultural production. This study employed the cointegration method and utilized annual data spanning a period of 37 years (1980 - 2016) including agriculture real gross domestic product as dependent variable, proxy for agriculture production, while explanatory variables are interest rate, number of employees in agriculture, real gross domestic product per capita as economic factors and rainfall and temperature as climate factors. This study employed cointegration method using Ordinary Least Square technique to estimate the long run and short run effects with Engle-Granger cointegration test and Error Correction Model, respectively. The cointegration test showed that there is a long-run cointegration between agriculture production and all explanatory variables. In the long run, interest rate, rainfall and temperature have negative and significant effects on agriculture production, while national income and employment have positive significant effects. In the short run, rainfall and temperature have negative and significant effects on agricultural production while employment has a positive and significant effect. Meanwhile, interest rate and income do not have significant effects on agriculture production in the short run. Therefore, the findings of the study highlighted that perfect information sharing of an accurate forecast on weather change, such as rainfall and temperature, is important to reduce the farmers’ losses. Based on accurate weather forecast from meteorology department, farmers can make a good plan on how to manage their agricultural production. In the economic perspective, the policy maker can establish special interest loan facilities to encourage farmers increase their investment on their agricultural production and adopt advance technology. Additionally, the authorities should make sure that there is no labour shortage in this sector. Because this is an upstream sector for food production, labour shortage in this sector may cause food shortage. This points to the possible implications of labour shortage in challenging the national food security issue.